(untitled) (Revista Electrónica REDINE, 2021)
Social responsibility in educational centers becomes a challenge, on whose training, analysis and reflection processes depends on having citizens capable of understanding their environment but also of transforming it. Sensitive to the problems of others, committed to the social development of their country and the social inclusion of the most vulnerable. Achievements in this area should be reflected in areas such as organizational functioning, training, and the impact on society. Therefore, the objective of this essay is to generate reflections on social responsibility in education, the evolution of the term, its impact on education and what could be built in terms of excellence in education, schools and society in general by assuming it as a model and guiding principle of doing in education.